Adhesión De Brackets A Esmalte Previamente Tratado Con Nanocomplejo De Fosfopéptido De Caseína-Fosfato De Calcio Amorfo (Cpp-Acp): Revisión Sistemática - Chica Llamas, Tomas David; Gomez Castro, Maria Del Rosario; Lastres Dominguez, Marvin David (Universidad Antonio Nariño, 2024)
Aim. To analyze the behavior of the adhesion values of brackets to enamel previously treated with the casein phosphopeptide-amorphous calcium phosphate nanocomplex. Methodology. The present systematic review was carried out following the protocols of the PRISMA statement (Preferred Reporting Items for Systematic reviews and Meta-Analyses). Systematic electronic searches were performed in 2 databases MEDLINE (via PUBMED) and Web Of Science (WOS), using key words (free terms) and MeSH (medical subject headings) such as “casein phosphopeptide - amorphous calcium phosphate”, “CPP- ACP”, “casein phosphopeptide - amorphous calcium phosphate and fluoride”, “CPP-ACPF”, “bonding”, “adhesion”, “bond strength”, “brackets”, “orthodontic braces”, “orthodontics”. Additionally, additional searches were performed on Google Scholar with related terms.